"Description of a Living Room and Kitchen" - Kendall, Sheila Marie (1978)
Dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial. -- Memorial University folklore student term paper. Deuxième d'une serie de trois dissertations faisant partie de la même accession - Associée aux photos P4826-P4832 -- Second in a series of three term papers comprising one accession - associated with photos P4826-P4832